Sputum Quality of The Anytime And Outset for Examination Acid-Resistance Bacilli - Leka Lutpiatina; Wahidah Wahidah; Nurhilaliah Nurhilaliah; Dinna Rakhmina; Rifqoh Rifqoh (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
Diagnosis Tuberculosis (TB) can establish by microscopic examination of acid-resistant bacilli in the patient's sputum. Sputum quality greatly affects the diagnosis of TB, but the sputum collected by patients at community health centers sometimes does not meet the sputum quality requirements. The objective of this study was to assess the quality of sputum anytime and outset sputum on acid-resistant bacilli examination, from volume, color and viscosity parameters. The type of research used is descriptive observational. Respondents were suspected TB patients at the Marabahan and Aluh-aluh Public Health Centers of South Kalimantan province, Indonesia. Sputum samples taken were sputum anytime the first and outset sputum. The variables in this study are volume, color, and viscosity of sputum. The coloring of acid-resistant bacilli method Ziehl Nielsen. The results of the acid-resistant bacilli examination on sputum (86 specimens) found positive one (13%), positive three (2%), negative (85%). In morning sputum (86 specimens) found positive one (14%), positive three (2%), negative (84%). Sputum quality when with the good category as much as 36% and the quality of morning sputum with the good category as much as 55%. Conclusion Sputum outset has better quality than sputum at the anytime.